Strategi Kepala Sekolah dalam Mengembangkan Karakter Disiplin Siswa di SD Negeri 2 Talise : The Principal's Strategy in Developing Student Discipline Character at Talise 2 Public Elementary School - Ni Luh Riska Vitriani; Yusdin Bin M. Gagaramusu; Dyah Rahmawati; Nashrullah Nashrullah; Ammar Abdullah Joni Guci (ITScience (Information Technology and Science), 2026)
This study aims to describe the principal's strategy in developing students' disciplined character at Talise 2 Public Elementary School and identify the obstacles encountered in its implementation. The study used a qualitative, descriptive design to gain a deep understanding of the phenomena in the field. The research subjects consisted of the principal, teachers, and students. Data collection techniques included observation, interviews, and documentation. In contrast, data analysis used the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data presentation, and conclusion. Data validity was tested through triangulation of sources and techniques. The results of the study indicate that the principal's strategy for developing students' disciplined character is carried out through several steps: the formulation and implementation of discipline policies; the principal's role modeling; coaching and habituation; the provision of educational rewards and sanctions; supervision and evaluation; and collaboration with parents. The strategy is implemented in an integrated, sustainable manner across daily school activities. However, the strategy's implementation still faces obstacles stemming from internal and external factors. Internal factors include low awareness of student discipline, a lack of responsibility, and poor formation of good study habits. Meanwhile, external factors include a lack of parental involvement in supporting children, suboptimal supervision, and inconsistent implementation of school rules. Based on these findings, increased consistency in strategy implementation, strengthened collaboration between schools and parents, and ongoing coaching are needed to ensure optimal and effective development of students' disciplined character.